HUBUNGAN MOTIVASI KERJA PERAWAT DENGAN KEPATUHAN PENGGUNAAN ALAT PELINDUNG DIRI PADA ERA PANDEMI COVID-19 DI RUMAH SAKIT ANANDA BEKASI - Widya Nofira Anwar (2021)
Compliance in the use of personal protective equipment for nurses greatly affects the process of preventing the transmission of disease or infection from the patient to the nurse on duty and can transmit the infection within the nurse to the patient, which is called nosocomial infection. Compliance really requires high motivation so that nurses avoid disease transmission when carrying out nursing actions. The purpose of this study was to identify the relationship between nurses' work motivation and compliance with the use of personal protective equipment during the covid-19 pandemic era at Ananda Hospital Bekasi. This study uses a descriptive correlation research design using a Cross Sectional approach. The sampling technique used is total sampling. Collecting data using a questionnaire and analyzed using the Chi-Square test. In this study, the results showed that there was a relationship between nurses' work motivation and compliance with the use of personal protective equipment at Ananda Hospital Bekasi with a p-value of 0.029 (OR = 5.714). The conclusion of this study is that nurses have high motivation and are obedient in using personal protective equipment on the basis of nurses' awareness in knowing the impact of not using personal protective equipment. It is hoped that nurses can maintain work motivation and compliance with the use of personal protective equipment in any situation, including during the COVID-19 pandemic, so that the services provided are better and patient safety can be guaranteed.